Vibrotactile perception thresholds: The tactile equivalent of audiometry - Brammer, A.J.; Piercy, J.E. (Canadian Acoustics, 2001)
An overview is given on the information that led to international acceptance of two, closely-related methods of measurement together with normative threshold values that may be used to identify changes from the vibrotactile perception thresholds (VPTs) of healthy persons. The information given is expected to rekindle interest in, and the development of, products designed to be used in analogous manner to audiometric instruments for determining hearing thresholds.